Diversification, family involvement and firm performance: Empirical evidence from Italian manufacturing firms. Issue 5 (13th June 2016) - Delbufalo, Emanuela; Poggesi, Sara; Borra, Simone
Abstract : Purpose: – The purpose of this paper is to investigate the effect of product and geographic diversification on the performance of Italian manufacturing firms and evaluate the moderating role of family involvement. Design/methodology/approach: – The hypotheses have been tested by using a fixed-effects panel data regression model. Findings: – Results show a linear relationship between product diversification and firm performance and an inverted U-shaped relationship between geographic diversification and firm performance. Moreover, when considering the status of the family firm, family ties have a negative moderating role on the performance of companies that are product and internationally diversified. Originality/value: – By providing theoretical explanations and empirical evidence, the study extends the diversification-performance research by testing this relationship in an unexplored context (i.e. Italy), and by identifying a still not well explored contingency factor (i.e. family involvement). In doing so, diversification and family involvement literatures are brought together and the results show the importance of the type of owner regarding the impact of product and international diversification on firm performance.